The Leadership of School Principal in The Education Era 4.0 - Ashdaq Fillah FR; Erny Roesminingsih; Meini Sondang Sumbawati (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Terminologically, the word 'leader' comes from the word